Frenemy at the gate: Invasion by Pheidole megacephala facilitates a competitively subordinate plant ant in Kenya. Issue 2 (1st December 2020) - Palmer, Todd M.; Riginos, Corinna; Milligan, Patrick D.; Hays, Brandon R.; Pietrek, Alejandro G.; Maiyo, Nelly J.; Mutisya, Samuel; Gituku, Benard; Musila, Simon; Carpenter, Scott; Goheen, Jacob R.
Abstract: Biological invasions can lead to the reassembly of communities and understanding and predicting the impacts of exotic species on community structure and functioning are a key challenge in ecology. We investigated the impact of a predatory species of invasive ant, Pheidole megacephala, on the structure and function of a foundational mutualism between Acacia drepanolobium and its associated acacia‐ant community in an East African savanna. Invasion by P. megacephala was associated with the extirpation of three extrafloral nectar‐dependent Crematogaster acacia ant species and strong increases in the abundance of a competitively subordinate and locally rare acacia ant species, Tetraponera penzigi, which does not depend on host plant nectar. Using a combination of long‐term monitoring of invasion dynamics, observations and experiments, we demonstrate that P. megacephala directly and indirectly facilitates T. penzigi by reducing the abundance of T. penzigi 's competitors ( Crematogaster spp.), imposing recruitment limitation on these competitors, and generating a landscape of low‐reward host plants that favor colonization and establishment by the strongly dispersing T. penzigi . Seasonal variation in use of host plants by P. megacephala may further increase the persistence of T. penzigi colonies in invaded habitat. The persistence of the T. penzigi–A. drepanolobium symbiosis in invaded areas afforded host plants some protection against herbivory by elephants ( Loxodonta africana ), a key browser that reduces tree cover. However, elephant damage on T. penzigi ‐occupied trees was higher in invaded than in uninvaded areas, likely owing to reduced T. penzigi colony size in invaded habitats. Our results reveal the mechanisms underlying the disruption of this mutualism and suggest that P. megacephala invasion may drive long‐term declines in tree cover, despite the partial persistence of the ant–acacia symbiosis in invaded areas.